Kernel Datum Transformation Considering Triangle Weight Centers - Uzel, Turgut; Eren, Kamil; Ürüşan, Ahmet Yücel; Gülal, Vahap Engin (Springer-Verlag Berlin, Heidelberger Platz 3, D-14197 Berlin, Germany, 2013)
When using GPS measurement data one always has to transform WGS84 coordinates to the ED50 coordinate system or to the desired local coordinate system or projection. The opposite is also needed. Several methods are available to shift coordinates from one geodetic datum to another. To develop these shifts coordinates of some physical locations must be known on the both datums. Two classes of datum shift methods are geometric transformation and polynomial fitting techniques. Here only a kernel geometric transformation method is discussed for the transformation datum shifts from the WGS84 to the ED50, or vice versa.
Keywords: Matematik; Mathematics; Physics; Fizik